Do local start-ups and knowledge spillovers matter for firm-level R&D investment?. (April 2022) - Crowley, Frank; Jordan, Declan
What happens to firm-level research and development (R&D) when urban locations have more knowledge spillovers and are more entrepreneurial? This article explores the potential tension between knowledge spillovers, start-ups and innovation effort in existing firms. The relationship is empirically tested using Swedish firm-level data and municipality-level data on start-ups. The results indicate that having more start-ups in urban municipalities is associated with lower firm-level R&D expenditure. However, this relationship is not linear, where the negative association between the level of new firm formation and firm-level R&D expenditure decreases with scale. This suggests that the relationship between local entrepreneurship and a business' R&D decisions is conditioned by the extent of that entrepreneurship.